ANALISIS KESIAPAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SD NEGERI TAUBNENO - Lakapu, Pifa A; Lasmawan, I Wayan; Suastra, I Wayan (Realita : Jurnal Bimbingan dan Konseling, 2024)
The independent learning curriculum is a new policy initiated by the government as one of the first steps in supporting the realization of national education goals, namely to make the nation's life smarter through liberating education. Teachers play an important role in both curriculum development and implementation. The aim of this research is to determine the readiness of Inpres Taubneno Elementary School teachers to implement the independent learning curriculum at Inpres Taubneno Elementary School. This type of research method is a qualitative-descriptive research method. The subjects in this research were teachers from grades 1 to IV and the principal of SD Inpres Taubneno. Data collection techniques in this research included interviews and documentation. This research shows that the teachers at SD Inpres Taubneno are ready to implement the independent learning curriculum. The teachers were prepared by attending offline workshops held at the school. Teacher preparation has not been optimal because they are still waiting for workshops to be held at schools for training in preparing teaching tools, but the independent learning curriculum has been implemented. The independent learning curriculum is implemented in stages so that the independent learning curriculum has been implemented in grades I and IV. The implementation of the independent learning curriculum at Inpres Taubneno Elementary School is known as the independent learning curriculum. From the results of this research, it can be concluded that the teachers at SD Inpres Taubneno are ready to implement the independent learning curriculum at school. However, the preparation of teachers at Inpres Taubneno Elementary School has not been optimal because Inpres Taubneno Elementary School teachers are still in the preparation stage.